PENGARUH METODE SCL DIPADU PETA KONSEP TERHADAP PEMAHAMAN BACAAN DAN MENULIS KARYA ILMIAH DALAM ERA MEA - Thahroni Thahroni; Rini Hartati (Psychopolytan : Jurnal Psikologi, 2018)
The use of scl methods combined with concept maps in the learning process becomes important because of the potential influence on the achievement of reading comprehension skills and writing scientific papers in the Era of the MEA. The purpose of the study was to see the effect of the scl method combined with a concept map of reading comprehension and writing scientific papers in the Era of the MEA. This research is a qualitative descriptive study. The results of the analysis show that there is an effect of the scl method combined concept maps of reading comprehension and writing scientific papers in the MEA Era. This means that scl methods combined with concept maps can improve reading comprehension skills and write scientific work in the MEA Era. This is because the scl method combined with a concept map is a learning approach that places students in the center of meaningful learning and learning activities by linking the concepts they have. For this reason, it is better for the teaching and learning process to integrate SCL methods with concept maps so that students are competent in the MEA Era because they have the ability to read and write scientific papers.